The Effect of Population Growth on Poverty Through Unemployment in East Java Province in 2017-2021 - Muhammad Al Faruq; Indah Yuliana (Journal of Social Research, 2023)
In 2022, the number of poor people in Java is ranked first in Indonesia, as many as 4. 181. 290 inhabitants (semester one) and 4. 236. 510 inhabitants (second semester). Factors are the cause of population growth and unemployment rates. Thisresearch aims to measure and determine the effect of population growth on poverty through unemployment rate as a mediating variable. Thisresearch uses quantitative methods. Data collection techniques wereobtained from the Central Statistics Agency (BPS) of East Java Province in the form of time series data from 201 to 2021. Data analysis techniques include classical assumption tests, path analysis tests and sobel tests through IBM SPSS Statistics 25 software and online statistics calculators. Theresultsof this research show that population growth has a positive and insignificant effect on poverty. The result of the regression coefficient is a positive direction of 0.324 with a significance value of 0.091 > 0.05. Inaddition, people without progress in other developmental factors will not increaseincome. Population growth has a positive and significant effect on the unemployment rate. Theresulting regression coefficient is a positive direction of 0.225 with a significance value of 0.004 < 0.05. The increase in population cannot be fully absorbed by the company. The unemployment rate has a negative and significant effect on poverty. Theregression coefficient is a negative direction of -0.948 with a significance value of 0.000 < 0.05. Unemployment is not necessarily low or underprivileged. Because they are from families withsufficient income. Population growth on poverty mediated by the unemployment rate is a negative effect and there is no mediated effect. The result of the sobel test obtained an Unstandardized Coefficients B value of -0.213 and an Unstandardized Coefficients Std value. Error of 0.085 > 0.05.